Fine-Mapping the Branching Habit Trait in Cultivated Peanut by Combining Bulked Segregant Analysis and High-Throughput Sequencing - Kayam, Galya; Brand, Yael; Faigenboim-Doron, Adi; Patil, Abhinandan; Hedvat, Ilan; Hovav, Ran (Frontiers in Plant Science, 2017)
The growth habit of lateral shoots (also termed "branching habit") is an important descriptive and agronomic character of peanut. Yet, both the inheritance of branching habit and the genetic mechanism that controls it in this crop remain unclear. In addition, the low degree of polymorphism among cultivated peanut varieties hinders fine-mapping of this and other traits in non-homozygous genetic structures. Here, we combined high-throughput sequencing with a well-defined genetic system to study these issues in peanut. Initially, segregating F2 populations derived from a reciprocal cross between very closely related Virginia-type peanut cultivars with spreading and bunch growth habits were examined. The spreading/bunch trait was shown to be controlled by a single gene with no cytoplasmic effect. That gene was named Bunch1 and was significantly correlated with pod yield per plant, time to maturation and the ratio of "dead-end" pods. Subsequently, bulked segregant analysis was performed on 52 completely bunch and 47 completely spreading F3 families. In order to facilitate the process of SNP detection and candidate-gene analysis, the transcriptome was used instead of genomic DNA. Young leaves were sampled and bulked. Reads from Illumina sequencing were aligned against the peanut reference transcriptome and the diploid genomes. Inter-varietal SNPs were detected, scored and quality-filtered. Thirty-four candidate SNPs were found to have a bulk frequency ratio value >10 and 6 of those SNPs were found to be located in the genomic region of linkage group B5. Three best hits from that over-represented region were further analyzed in the segregating population. The trait locus was found to be located in a 1.1 Mbp segment between markers M875 (B5:145,553,897; 1.9 cM) and M255 (B5:146,649,943; 2.25 cM). The method was validated using a population of recombinant inbreed lines of the same cross and a new DNA SNP-array. This study demonstrates the relatively straight-forward utilization of bulk segregant analysis for trait fine-mapping in the low polymeric and heterozygous germplasm of cultivated peanut and provides a baseline for candidate gene discovery and map-based cloning of Bunch1.